Management of urogenital hygiene health education to improve knowledge and prevent urinary tract infection in patient with chronic kidney disease - Allyarista, Dhea Firnanda Airin; Asmaningrum, Nurfika; Ardiana, Anisah; Darmawan , I Kade Iman (Utan Kayu Publishing, 2024)
Urinary Tract Infections (UTIs) are a prevalent form of Healthcare-Associated Infections (HAIs) in patients with chronic kidney disease (CKD), especially those undergoing urinary catheterization. It is estimated that UTIs affect up to 25% of catheterized patients, significantly impacting morbidity and healthcare costs (World Health Organization, 2021). This study aims to determine how health education regarding urogenital hygiene can increase knowledge and prevent infection for patients undergoing urinary catheterization. This research is quantitative descriptive using a case study approach. A one-group pre-test post-test design was employed to collect data through the administration of pre-test and post-test knowledge assessments before and after health education. The results demonstrated a significant increase in knowledge scores from 67 to 93, indicating the effectiveness of health education in enhancing knowledge about urogenital hygiene. Furthermore, observation of signs and symptoms of UTIs showed a decrease in symptoms during the patient's treatment, highlighting the positive impact of health education. Providing urogenital hygiene education effectively increases knowledge and mitigates the risk of UTIs during patient care.